Methemoglobinemia associated with metaflumizone poisoning. (April 2014) - Oh, J. S.; Choi, K. H.
Abstract: Context. Metaflumizone is a voltage-dependent sodium channel blocker insecticide, which is chemically similar to indoxacarb. Although indoxacarb poisoning is known as a cause of methemoglobinemia, the effect of metaflumizone poisoning in humans is still unknown. Case details. A 57-year-old man presented with a decreased mentality following ingestion of 100 ml of metaflumizone, 150 ml of glyphosate and alcohol. Although initial methemoglobin (MetHb) level was slightly higher than the normal limit, it gradually rose to reach a maximum level of 27.8%, on the 19 h after ingestion. After hemodialysis, MetHb level was reduced to 15.8%, which decreased further to the level of 6%, following methylene blue administration. Discussion. Metaflumizone shares a similar chemical structure to indoxacarb, which is known to be a cause of methemoglobinemia. Physicians should be alert for the development of methemoglobinemia in symptomatic patients when facing potential pesticide poisoning such as metaflumizone poisoning.